On the Relationship of Arctic Polynyas and Atmospheric Rivers. Analyzing Arctic polynya and atmospheric river activity during winter seasons between 1979 and 2019 - Engelsson, Judit; Strandvik, Martine; Winnes, Tyra (My University, 2026)
Atmospheric rivers [ARs] are narrow and long regions characterized by unusually high moisture transport. ARs have over the last decades experienced a poleward shift and are because of this becoming more important to study in the higher latitudes. Arctic polynyas, openings in the sea ice cover, have simultaneously increased in frequency. However, the effect of ARs on arctic polynyas have not been sufficiently studied. In this study, we investigate the potential relationship between ARs and Arctic polynyas. Using a public dataset based on satellite data and one AR-catalogue from the ARTMIP project, we retrieved polynya and AR activity for the winter seasons between 1979 and 2019. Initially, an Arctic-wide analysis was made. We analyzed the general characteristics of ARs and polynyas independent of their location. Then we examined the relationship between ARs and polynya opening events, here defined as the polynya variable changing from closed to open for any grid cell. Subsequently, we identified nine regions with high polynya activity and conducted a similar analysis for these individually. Our results show a positive correlation (r ≈ 0.49) between AR frequency and polynya opening events across the Arctic. Over a period of four days before the opening, ARs are present during approximately 36% of polynya opening events. This is a substantial increase compared to the baseline AR occurrence, which is almost 7%. The relationship between ARs and polynya openings is strongest one day prior to the opening event. The regional analysis reveals high variability, with five out of nine regions showing positive corre lations between AR frequency and polynya opening events, while the four remaining exhibit weak or negative correlations. The highest correlation is observed in Franz Josef Land, which has a high amount of both polynya openings and ARs. Furthermore, the regions Kara Sea, Svalbard and Chukchi Sea show a large increase in AR activity over polynya opening locations during the upcoming days of the opening event. These findings suggest that ARs contribute to the triggering or enhancement of polynya openings. Further investigation is needed, as investigating ARs’ effect on polynya openings as opposed to expansion of already existing polynyas, to better understand the dynamics of Arctic polynyas and AR activity.
Keywords: On the Relationship of Arctic Polynyas and Atmospheric Rivers. Analyzing Arctic polynya and atmospheric river activity during winter seasons between 1979 and 2019